In Silico Evaluation of the Antibacterial Potential of Methanolic Lo’i-Keta Extract Against DNA Gyrase in Staphylococcus aureus and Pseudomonas aeruginosa - M. Agung Wisnu Pratama; Rozikin; Made Ayu Mirah Wulandari; Resna Hermawati (Department of Biology Education, FSTT, Mandalika University of Education, Indonesia., 2026)
This study aimed to evaluate the antibacterial potential of bioactive compounds identified in the methanolic extract of lo’i-keta against DNA gyrase from Staphylococcus aureus (PDB ID: 3G75) and Pseudomonas aeruginosa (PDB ID: 6M1S) using an in silico approach. Bioactive compounds were identified by gas chromatography–mass spectrometry (GC–MS). Ligand preparation and molecular docking were subsequently performed using PyRx 0.8, while ligand–protein interactions were visualized using Discovery Studio. Ciprofloxacin was used as the positive control. GC–MS analysis detected 20 compound peaks, of which 13 compounds were validated and included in the docking analysis. Molecular docking results showed that cyclooctacosane exhibited the strongest binding affinity toward the DNA gyrase of S. aureus and P. aeruginosa, with binding energies of −8.3 and −8.2 kcal/mol, respectively. These values were more favorable than those of ciprofloxacin, which showed binding affinities of −7.7 and −7.4 kcal/mol, respectively. In addition, dioctyl benzene-1,2-dicarboxylate displayed a residue interaction pattern similar to that of ciprofloxacin within the active site of DNA gyrase. Hexadecanoic acid (palmitic acid) exhibited a more moderate binding affinity but was present at a relatively high abundance in the extract. These findings indicate that several bioactive compounds in lo’i-keta may form stable interactions with DNA gyrase, supporting its potential as a molecular target for antibacterial activity. Based on the in silico results, cyclooctacosane was identified as the leading candidate DNA gyrase inhibitor, while dioctyl benzene-1,2-dicarboxylate and hexadecanoic acid may serve as supporting candidates for the development of lo’i-keta-based antibacterial agents. This study provides a scientific basis for the traditional use of lo’i-keta; however, further in vitro and in vivo investigations are required to validate these findings.